Hypoxia-Induced Upregulation of lncRNA ELFN1-AS1 Promotes Colon Cancer Growth and Metastasis Through Targeting TRIM14 via Sponging miR-191-5p - Jing, Xu; Du, Lutao; Shi, Shuang; Niu, Aijun; Wu, Jing; Wang, Yunshan; Wang, Chuanxin (Frontiers in Pharmacology, 2022)
Hypoxia is identified as one of the microenvironmental features of most solid tumors and involved in tumor progression. In the present research, we demonstrate that lncRNA Extracellular leucine rich repeat and fibronectin type III domain containing 1-antisense RNA 1 (ELFN1-AS1) is up-regulated by hypoxia in colon cancer cells. Knockdown of ELFN1-AS1 inhibits the proliferation and invasion, and induces the apoptosis of colon cancer cells. Transfection of ELFN1-AS1 siRNA in hypoxic colon cancer cells can reduce cell proliferation and restore the invasion to non-hypoxic levels. FISH results show that ELFN1-AS1 is distributed in cytoplasm of colon cancer cells, so we continue to analyze the potential target for ELFN1-AS1 as a competing endogenous RNA (ceRNA). MiR-191-5p contains a binding sequence with ELFN1-AS1 and is down-regulated by ELFN1-AS1 in colon cancer cells. Then, there is a binding site between miR-191-5p and the 3’UTR region of tripartite motif TRIM 14 (TRIM14). The expression of TRIM14 is inhibited by ELFN1-AS1 siRNA or miR-191-5p mimics in LoVo and HT29 cells. The treatment of miR-191-5p inhibiter in ELFN1-AS1 knockdown cells can significantly increase cell proliferation and invasion ability. Overexpression of TRIM14 in miR-191-5p-mimics-treated cells can rescue the inhibition of proliferation and invasion caused by miR-191-5p-mimics. In conclusion, ELFN1-AS1 operates as a downstream target of hypoxia, promotes the proliferation and invasion, and inhibits the apoptosis through upregulating TRIM14 by sponging miR-191-5p in colon cancer cells. Our results enrich our understanding to the colon cancer progression and provide potential targets for clinical treatment of colon cancer.